KAJIAN ANALISIS PELILINAN TERHADAP SIFAT FISIK-KIMIA JERUK KEPROK DI KABUPATEN TAPANULI SELATAN - Imelda Sari Harahap (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2018)
Research studies conducted to analyze the influence of research on the physics- chemical tangerine. This research was conducted in chemistry labolatory of Muhammadiyah University in South Tapanuli. The observed variables change in physical characteristic of the fruit include (texture, weight, brightness of the fruit), the cemical characteristic (moisture content) and the fruit’s shelf life. primary data obtained directly with experiments in chemical labolatories, The observed data were texture , weight, clour fruit, and fruit’s shelf life at room temperature . To analyze the effect of pelilinan on the physical – chemical characteristic of tangerine was done by ANOVA it was analyzed with standar deviation and fuadvanceds used BNT test level 5 Keywords : pelilinan, the physical – chemical, tangerine